A Critical Reanalysis of “a Test of two Postulates Underlying Expectancy Theory” - Liddell, William W.; Solomon, Robert J. (Academy of Management Journal, 1977)
The article presents a commentary on the article ?A Test of Two Postulates Underlying Expectancy Theory,? by F. A. Starke and O. Behling. In the original article Starke and Behling attempted to test the transitivity and independence properties of an expectancy model. The authors contend that they instead reported another methodologically faulted test of the model's ability to predict behavior. They explain that part of their test of the independence postulate was inappropriate and their remaining evidence is questionable.